2D NMR study on chemical structure of the co-oligomers from carbon dioxide/propylene oxide/diol synthesized by a metal-free catalyst. (March 2022) - Alferov, Kirill; Wang, Shuanjin; Han, Dongmei; Guan, Shanyue; Xiao, Min; Meng, Yuezhong
Abstract: Co-oligomers of carbon dioxide and propylene oxide with high carbonate content and terminated by hydroxyl groups are practically important polyols to synthesize block copolymers. Despite this, the 1 H and 13 C spectra of such co-oligomers have not been described in detail so far. In this article, a new metal-free synthesis of carbon dioxide/propylene oxide co-oligomers by a triethylborane/organic base (organic base is PPNCl) catalytic system in the presence of diols (1, 2-propanediol, 1, 4-butanediol) is briefly introduced. The resonances in the 1 H and 13 C NMR spectra of the synthesized products were assigned using 2D NMR spectrometry methods (COSY, TOCSY, selective HMBC, and HSQC). As a result, the signals of different types of chain ends and of propylene oxide units forming ether linkages were found in addition to the peaks of carbonate blocks. Moreover, our study confirmed the occurrence of an efficient chain transfer during the co-oligomerization, which is additionally supported by MALDI TOF mass spectrometry results. Highlights: CO2 /propylene oxide/diol co-oligomers were synthesized by metal free catalysis. The signals in the NMR spectra of the co-oligomers were assigned in detail. Chain transfer by diols operates in the course of the reaction.